Efek kombinasi Amoksisilin dan Kloramfenicol terhadap pertumbuhan bakteri Salmonela thypi - Bambang Friambodo; Yudi Purnomo; Ariani Ratri Dewi (JIMR - Journal of Islamic Medicine Research, 2017)
AbstractIntroduction :Thypoid fever is one of endemic infection diseases caused bybacteria Salmonela thypi. Occasionally, Thypoid fever is accompanied others infection therefore antibiotic combination is often used to eradicate the infection. Combination of Amoxicillin and Chloramphenicol widely used for treatment of Thypoid fever. Based on theory, the combinationproduces antagonist interaction, however it is still used by Clinicans due to mixed infection. The objective of study to know the antibacterial effect of combination Amoxicillin and Chloramphenicol onSalmonela thypigrowth. Method:The research was done by using disc diffusion methods with Muller Hinton media. Amoxicillin 0,05 µg/ml, 0,1 µg/ml, 0,2 µg/ml , Chloramphenicol 1,25 µg/ml, 2,5 µg/ml, 5 µg/ml and their combinations were tested on Salmonela thypi culture. After 24 hour of administration, antibacterial effect was observed by measuring inhibition zone on bacteria culture. The result of study was tested statistically with One WayANOVA (p=0.05) followed by the test of student-t (t-test) and test of least real difference (LSD) to find out the significance of each groups. Result and discussion: Antibiotic combinationof Amoxicillin and Chloramphenicol have anti-bacterial effect lower than single antibiotic. B-lactam antibiotic like Amoxicillin require that the cell be growing and dividing in order to havea bactericidal action. Chloramphenicolcause slow growth of Salmonella thypiand then impairs bactericidal effect of Amoxicillin. Among combination of antibiotic tested, Amoxicillin 0,5 µg/mland Chloramphenicol 5 µg/ml has antibacterial effect stronger than others. It was caused by the difference dose of bactericide and bacteriostatic used. Conclusion:Combination of Amoxicillin and Chloramphenicol has antibacterial effect lower than the single antibioticgroup on Salmonela thypi.The combination of high dose of Chloramphenicoland low dose of Amoxicillin shows antibacterial effect in the moderate category.Key words:Amoxicillin,Chloramphenicol, Combination, Salmonela thypi.